TRANSFER, COMPULSORY ALIENATION OR SEIZURE OF PROPERTY DURING MARTIAL LAW - Litvinova, Iryna; Holukh, Vladyslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article on the transfer, expropriation or seizure of property during martial law is to disclose the legal, economic and social aspects related to this process in emergency situations. The article analyzes the legal grounds and mechanisms for implementing such actions, considers the impact on property owners, and assesses the effectiveness and fairness of these measures in terms of protecting national security and public interests. This topic is important for understanding the balance between state needs and the rights of citizens, especially in the context of current challenges and threats. Research methods: the article uses the methods of comparative analysis and legal modeling, which allow for a detailed study of legislative norms, practical examples and consequences of expropriation of property during martial law. The author also uses the method of document analysis for a deeper understanding of the legal and socio-economic aspects of this issue. The results of the study show that the forced alienation or seizure of property during martial law, although justified from the point of view of national security, raises significant legal and social challenges. In particular, it was found that existing legal mechanisms do not always provide adequate compensation to owners, which can lead to social tension and a decrease in trust in state institutions. The analysis showed that successful implementation of such measures requires transparent procedures, clear regulation and constant monitoring to minimize negative consequences for citizens and the economy. Discussion: the discussion revealed that while the expropriation of property during martial law is a necessary measure to ensure national security, there is a need to improve the legal and administrative mechanisms for its implementation. It is important that the expropriation processes are as transparent and fair as possible, with clear criteria for determining the objects of expropriation and compensation mechanisms for affected owners. Particular attention should be paid to preventing abuses and corruption in this area, as well as to ensuring a proper balance between the interests of the state and the rights of citizens.